Participation in collaborative fisheries research improves the perceptions of recreational anglers towards marine protected areas - Erin M. Johnston; Grant T. Waltz; Rosamaria Kosaka; Ellie M. Brauer; Shelby L. Ziegler; Erica T. Jarvis Mason; Hunter S. Glanz; Lauren Zaragoza; Allison N. Kellum; Rachel O. Brooks; Brice X. Semmens; Christopher J. Honeyman; et al. (Frontiers in Marine Science, 2024)
Collaborative fisheries research programs engage stakeholders in data collection efforts, often with the benefit of increasing transparency about the status and management of natural resources. These programs are particularly important in marine systems, where management of recreational and commercial fisheries have historically been contentious. One such program is the California Collaborative Fisheries Research Program (CCFRP), which was designed in 2006 to engage recreational anglers in the scientific process and evaluate the efficacy of California’s network of marine protected areas. CCFRP began on the Central Coast of California and expanded statewide in 2017 to include six partner institutions in three regions: Northern, Central, and Southern California. To date, over 2,000 volunteer anglers have participated in the program, with many anglers volunteering for multiple years. However, the impacts of outreach, education, and collaborative research on those anglers at the statewide scale are currently unknown. Thus, the objective of the current study was to survey the statewide pool of volunteer anglers to assess the degree to which participation in CCFRP has influenced angler perceptions of MPAs, fisheries management, and conservation. We received 259 completed surveys out of a pool of 1,386 active anglers, equating to an 18.7% response rate. Participation in CCFRP resulted in a significant, positive impact on anglers’ attitudes towards MPAs in California across all regions. Anglers who participated in six or more CCFRP fishing trips had a more positive perception of MPAs than those who participated in fewer trips. Volunteer anglers across all regions perceived that they caught larger fishes, a higher abundance of fishes, and a greater diversity of species inside MPAs, consistent with the ecological findings of the program. These results highlight the benefits of involving community members in collaborative scientific research. Collaboration between researchers and the broader community increases transparency and trust between stakeholders, and results in greater understanding of natural resource dynamics, ultimately producing better management outcomes.

SARS-CoV-2 vaccinated hamsters show distinctive lung pathology with Th-2 skewed immune response following infection - R. de Jong; S. Vreman; K. Wiese; B. Small; N. Gerhards; K. Bewley; Y. Hall; F.J. Salguero; M. Caroll; N. Oreshkova (Journal of Comparative Pathology, 2023)

Characterisation of neonatal cardiac dynamics using ordinal partition network - Laurita dos Santos; Débora C. Corrêa; David M. Walker; Moacir F. de Godoy; Elbert E. N. Macau; Michael Small (Medical & Biological Engineering & Computing, 2022)

Addressing key issues in the consanguinity-related risk of autosomal recessive disorders in consanguineous communities: lessons from a qualitative study of British Pakistanis - A. Darr; N. Small; W. I. U. Ahmad; K. Atkin; P. Corry; B. Modell (Journal of Community Genetics, 2016)

Examining the family-centred approach to genetic testing and counselling among UK Pakistanis: a community perspective - A. Darr; N. Small; W. I. U. Ahmad; K. Atkin; P. Corry; J. Benson; R. Morton; B. Modell (Journal of Community Genetics, 2013)

Rates and controls of nitrification in a large oligotrophic lake - Gaston E. Small; George S. Bullerjahn; Robert W. Sterner; Benjamin F. N. Beall; Sandra Brovold; Jacques C. Finlay; Robert M. L. McKay; Maitreyee Mukherjee (Limnology and Oceanography, 2013)
Recent discoveries have altered prevailing paradigms concerning the conditions under which nitrification takes place and the organisms responsible for nitrification in aquatic ecosystems. In Lake Superior, nitrate () concentrations have increased fivefold in the past century. Although previous evidence indicated that most is generated by nitrification within the lake, important questions remain concerning the magnitude and controls of nitrification, and which microbial groups are primarily responsible for this process. We measured water‐column nitrification rates in the western basin of Lake Superior during five research cruises from November 2009 to March 2011. Using in situ bottle incubations at 10 depths, we quantified nitrification rates using both the oxidation of 15 N‐labeled ammonium () and the uptake of 14 C associated with nitrification. Average rates of oxidation ranged from 18–34 nmol N L −1 d −1 across the five cruises, similar to values reported for the coastal ocean, and two orders of magnitude lower than values reported from other lakes. Low nitrification rates observed in the epilimnion corresponded to the absence of ammonium‐oxidizing archaea and nitrite‐oxidizing bacteria. The measured rates of nitrification are > 50‐fold greater than the long‐term rise in the lake, indicating that N is actively cycling and that long‐term change in this ecosystem is mediated by internal dynamics.

Tobacco smoke exposure induces nicotine dependence in rats - Elysia Small; Hina P. Shah; Jake J. Davenport; Jacqueline E. Geier; Kate R. Yavarovich; Hidetaka Yamada; Sreedharan N. Sabarinath; Hartmut Derendorf; James R. Pauly; Mark S. Gold; Adrie W. Bruijnzeel (Psychopharmacology, 2010)

KILLER WHALES AND MARINE MAMMAL TRENDS IN THE NORTH PACIFIC—A RE‐EXAMINATION OF EVIDENCE FOR SEQUENTIAL MEGAFAUNA COLLAPSE AND THE PREY‐SWITCHING HYPOTHESIS - Paul R. Wade; Vladimir N. Burkanov; Marilyn E. Dahlheim; Nancy A. Friday; Lowell W. Fritz; Thomas R. Loughlin; Sally A. Mizroch; Marcia M. Muto; Dale W. Rice; Lance G. Barrett‐Lennard; Nancy A. Black; Alexander M. Burdin; et al. (Marine Mammal Science, 2007)
Springer et al . (2003) contend that sequential declines occurred in North Pacific populations of harbor and fur seals, Steller sea lions, and sea otters. They hypothesize that these were due to increased predation by killer whales, when industrial whaling's removal of large whales as a supposed primary food source precipitated a prey switch. Using a regional approach, we reexamined whale catch data, killer whale predation observations, and the current biomass and trends of potential prey, and found little support for the prey‐switching hypothesis. Large whale biomass in the Bering Sea did not decline as much as suggested by Springer et al ., and much of the reduction occurred 50–100 yr ago, well before the declines of pinnipeds and sea otters began; thus, the need to switch prey starting in the 1970s is doubtful. With the sole exception that the sea otter decline followed the decline of pinnipeds, the reported declines were not in fact sequential. Given this, it is unlikely that a sequential megafaunal collapse from whales to sea otters occurred. The spatial and temporal patterns of pinniped and sea otter population trends are more complex than Springer et al . suggest, and are often inconsistent with their hypothesis. Populations remained stable or increased in many areas, despite extensive historical whaling and high killer whale abundance. Furthermore, observed killer whale predation has largely involved pinnipeds and small cetaceans; there is little evidence that large whales were ever a major prey item in high latitudes. Small cetaceans (ignored by Springer et al .) were likely abundant throughout the period. Overall, we suggest that the Springer et al . hypothesis represents a misleading and simplistic view of events and trophic relationships within this complex marine ecosystem.

Recombination within sympatric cryptic species of the insect pathogenic fungus Metarhizium anisopliae - Michael J. Bidochka; Cherrie‐Lee N. Small; Michael Spironello (Environmental Microbiology, 2005)
Summary Metarhizium anisopliae is an insect pathogenic fungus with a worldwide distribution. It is being developed and used as a biocontrol agent against a wide range of insect pests but relatively little is known of the life history of this fungus. We tested hypotheses concerning reproductive isolation and recombination in a sample of heat‐active (ability to grow at 37°C) and cold‐active (ability to grow at 8°C) sympatrically occurring isolates of M. anisopliae from Ontario, Canada by assaying nucleotide sequence variation at six polymorphic loci: the internally transcribed spacer (ITS) region of the nuclear ribosomal DNA repeat, and portions of calmodulin (CAL), chitin synthase (CHS), subtilisin‐like protease (PR1), neutral trehalase (NTL) and actin (ACT)‐encoding genes. The most parsimonious trees constructed showed a topology consistent with the heat‐active and cold‐active isolates as two monophyletic groups. We then applied Genealogical Concordance Phylogenetic Species Recognition (GCPSR) to the genealogical trees and concluded that the transition from concordance among branches to incongruity among branches delimited two species of M. anisopliae within Ontario. The GCPSR of two species was supported by intraspecific incongruity within each species when tested using the Partition Homogeneity test, indicating recombination. The GCPSR of two species also corresponded to the heat‐active and cold‐active groups. As the groups are morphologically indistinguishable we applied the term ‘cryptic species’. Therefore, the sympatrically occurring heat‐active and cold‐active isolates represent different cryptic species with a history of recombination among isolates within each species.

Nucleotide Sequence Variation Does Not Relate to Differences in Kinetic Properties of Neutral Trehalase from the Insect Pathogenic Fungus Metarhizium anisopliae - Cherrie-Lee N. Small; Nickett Donaldson; Michael J. Bidochka (Current Microbiology, 2004)

Crystal structure of bullfrog M ferritin at 2.8 Å resolution: analysis of subunit interactions and the binuclear metal center - Y. Ha; Dashuang Shi; George W. Small; Elizabeth C. Theil; N. M. Allewell (JBIC Journal of Biological Inorganic Chemistry, 1999)